THE KNOWLEDGE OF 5th-GRADE STUDENTS IN TASKS OF GRAMMATICAL JUDGMENT AND CORRECTION - Arvigo, Maria Claudia; Capellini, Simone Aparecida [UNESP] (Univ Estadual Parana, Escola Musica & Belas Artes Parana, 2017)
Nowadays, the metalinguistic awareness has been highlighted in studies on development of literacy abilities. This research aimed to understand and compare syntactic knowledge using tasks of grammatical judgment and correction. Subjects were 58 5th-grade students (29 students from a municipal school in Jundiai and 29 students from a state school in Campinas, both in Sao Paulo, Brazil). Statistical analysis showed an inferior performance compared to what is seen in the literature, representing that these students do not dissociate between spoken grammar and written grammar. However, the materials used by this research showed to be an important and satisfactory instrument to know the students' syntactic knowledge.
Keywords: Metalinguistic awareness; Syntactic knowledge; Morphosyntactic tasks